The Effect of Long-Term Monitoring on the Correction of Medication and Treatment among Patients with Intractable Epilepsy - Mohammad Zarea; Jafar Mehvari; Nasrin Oujifard (مجله دانشکده پزشکی اصفهان, 2018)
Background: Studies show that a considerable part of intractable epilepsy have psychological cause, and long-term monitoring can separate pseudoseizure from epilepsy. So, this study aimed to detect the effect of long-term monitoring on correction of medication among patients with intractable epilepsy.